Paediatricians' practices and knowledge of corticosteroids: A national survey. (28th July 2020) - Sekler, Opal; Segev‐Becker, Anat; Interator, Hagar; Brener, Avivit; Schachter‐Davidov, Anita; Elkon‐Tamir, Erella; Lebenthal, Yael
Abstract: Aim: To explore corticosteroid prescription practices and knowledge among paediatricians. Methods: The Paediatricians Corticosteroids Survey, a cross‐sectional, web‐based survey distributed to Israeli paediatricians between February and July 2018. Results: Three hundred and forty‐nine paediatricians (105 general paediatricians, 207 subspecialists and 37 paediatric endocrinologists) participated. Two hundred and three (58.2%) had >10 years of paediatric clinical experience and treated >60 patients/wk on average, 175/318 (55%) prescribed corticosteroids to >10% of their patients. On knowledge items, 11/266 (4.1%) responded 'not sure' when tapering of steroids is required, 22/268 (8.2%) to what 'stress dose' meant and 27/268 (10.1%) when a stress dose is required. Multivariate linear analysis showed higher scores were associated with training in paediatric endocrinology (β = 2.271, P  = 0.032); medical practice only in a subspecialty (β = 1.909, P  = 0.041) or in both general paediatrics and a subspecialty (β = 2.023, P  = 0.014), compared to general paediatrics alone and medical studies in Israel (β = 1.059, P  = 0.035). Overall, 96.2% thought continued medical education (CME) sessions would be helpful. Conclusion: Our findings suggest that despite clinical experience with corticosteroid usage, respondents demonstrated gaps in knowledge for potentially life‐threatening situations. Corticosteroid‐based CME programs are warranted to improve paediatricians' knowledge and patient management.